Avaliação e eficiência do tratamento físico químico de efluente pela técnica de eletrocoagulação com diferentes eletrólitos suportes - Finger, Amanda (2018)
Beauty salon effluents have a complex diverse containing a high concentration of nonbiodegradable organic material. The release of these effluents in the urban sewage system proves to be inadequate, in addition to contributing to the increase of environmental pollution. In this sense, this experimental study investigated the feasibility of the use of electrocoagulation in the treatment of sewage released by beauty salons. An electrolytic bench reactor was developed with electrodes of aluminium plates arranged in a monopolar way, with 3-volt fixed voltage and variable current. The electrical conductivity of 247 μS cm-1 required the use of supporting electrolytes to increase the efficiency in the electrolytic reactions. Effluents were treated by electrocoagulation without the use of supporting electrolytes, with sufficient NaCl supporting electrolyte for a conductivity of 500 μS cm-1 , with sufficient NaCl for 1,000 μS cm-1 and with hydrated lime solution at 5, 15 and 30 minutes of exposure to the treatment. The analysis of the crude effluents showed BOD5,20 concentrations of 300 mg O2 L -1 , COD of 2,100 mg O2 L -1 and COD/BOD5.20 ratio of 6.2. Although the value of BOD5.20 is close to that of domestic effluent, COD and COD/BOD5,20 ratio confirm the highly recalcitrant organic material present. The best performance was observed 15 minutes after starting electrocoagulation with NaCl enough for 1,000 μS cm-1 , with 90% apparent color removal, 83% turbidity and 94% COD, while no significant efficiency gains were observed with periods longer than 15 minutes. Electrocoagulation has been shown to be a viable physicochemical treatment alternative for beauty salon effluents, liable to real-scale reproduction and implementation in this type of facilities.